Prx1-Expressing Progenitor Primary Cilia Mediate Bone Formation in response to Mechanical Loading in Mice - Emily R. Moore; Julia C. Chen; Christopher R. Jacobs (Stem Cells International)
Increases in mechanical loading can enhance the addition of new bone, altering geometry and density such that bones better withstand higher forces. Bone-forming osteoblasts have long been thought to originate from progenitors, but the exact source is yet to be identified. Previous studies indicate osteogenic precursors arise from Prx1-expressing progenitors during embryonic development and adult fracture repair. However, it is unknown whether this cell population is also a source for mechanically induced active osteoblasts. We first identified that Prx1 is expressed in skeletally mature mouse periosteum, a thin tissue covering the surface of the bone that is rich in osteoprogenitors. We then traced Prx1 progenitor lineage using a transgenic mouse model carrying both a Prx1-driven tamoxifen-inducible Cre and a ROSA-driven lacZ reporter gene. Cells that expressed Prx1 when compressive axial loading was applied were detected within the cortical bone days after stimulation, indicating osteocytes are of Prx1-expressing cell origin. In addition, we evaluated how these cells sense and respond to physical stimulation in vivo by disrupting their primary cilia, which are antenna-like sensory organelles known to enhance mechanical and chemical signaling kinetics. Although Prx1-driven primary cilium disruption did not affect osteoblast recruitment to the bone surface, the relative mineral apposition and bone formation rates were decreased by 53% and 34%, respectively. Thus, this cell population contributes to load-induced bone formation, and primary cilia are needed for a complete response. Interestingly, Prx1-expressing progenitors are easily extracted from periosteum and are perhaps an attractive alternative to marrow stem cells for bone tissue regeneration strategies.